N-Acetylcysteine Protects Bladder Epithelial Cells from Bacterial Invasion and Displays Antibiofilm Activity against Urinary Tract Bacterial Pathogens - Arthika Manoharan; Samantha Ognenovska; Denis Paino; Greg Whiteley; Trevor Glasbey; Frederik H. Kriel; Jessica Farrell; Kate H. Moore; Jim Manos; Theerthankar Das (MDPI AG, 2021)
Introduction: Urinary tract infections (UTIs) affect more than 150 million individuals annually. A strong correlation exists between bladder epithelia invasion by uropathogenic bacteria and patients with recurrent UTIs. Intracellular bacteria often recolonise epithelial cells post-antibiotic treatment. We investigated whether N-acetylcysteine (NAC) could prevent uropathogenic E. coli and E. faecalis bladder cell invasion, in addition to its effect on uropathogens when used alone or in combination with ciprofloxacin. Methods: An invasion assay was performed in which bacteria were added to bladder epithelial cells (BECs) in presence of NAC and invasion was allowed to occur. Cells were washed with gentamicin, lysed, and plated for enumeration of the intracellular bacterial load. Cytotoxicity was evaluated by exposing BECs to various concentrations of NAC and quantifying the metabolic activity using resazurin at different exposure times. The effect of NAC on the preformed biofilms was also investigated by treating 48 h biofilms for 24 h and enumerating colony counts. Bacteria were stained with propidium iodide (PI) to measure membrane damage. Results: NAC completely inhibited BEC invasion by multiple E. coli and E. faecalis clinical strains in a dose-dependent manner (p < 0.01). This was also evident when bacterial invasion was visualised using GFP-tagged E. coli. NAC displayed no cytotoxicity against BECs despite its intrinsic acidity (pH ~2.6), with >90% cellular viability 48 h post-exposure. NAC also prevented biofilm formation by E. coli and E. faecalis and significantly reduced bacterial loads in 48 h biofilms when combined with ciprofloxacin. NAC visibly damaged E. coli and E. faecalis bacterial membranes, with a threefold increase in propidium iodide-stained cells following treatment (p < 0.05). Conclusions: NAC is a non-toxic, antibiofilm agent in vitro and can prevent cell invasion and IBC formation by uropathogens, thus providing a potentially novel and efficacious treatment for UTIs. When combined with an antibiotic, it may disrupt bacterial biofilms and eliminate residual bacteria.